2021
DOI: 10.3390/biomedicines9030327
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Treatment of Azathioprine in Rats Induces Vessel Mineralization

Abstract: Medial vascular calcification (mVC) is closely related to cardiovascular disease, especially in patients suffering from chronic kidney disease (CKD). Even after successful kidney transplantation, cardiovascular mortality remains increased. There is evidence that immunosuppressive drugs might influence pathophysiological mechanisms in the vessel wall. Previously, we have shown in vitro that mVC is induced in vascular smooth muscle cells (VSMCs) upon treatment with azathioprine (AZA). This effect was confirmed i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…This could be confirmed in the ex vivo setting with Nlrp3 −/− mice, where the calcification induction by DOX is also inhibited compared to control mice. This finding is comparable to our previous results regarding the stressor azathioprine, whose calcifying effect could also no longer be seen in aortic rings from Nlrp3 −/− mice ( 35 ). Therefore, Il-1β appears to be a very important effector cytokine, especially for the maintenance of a SASP after primary initiation of the SASP by the induction of “inflammaging” due to a cellular stressor.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This could be confirmed in the ex vivo setting with Nlrp3 −/− mice, where the calcification induction by DOX is also inhibited compared to control mice. This finding is comparable to our previous results regarding the stressor azathioprine, whose calcifying effect could also no longer be seen in aortic rings from Nlrp3 −/− mice ( 35 ). Therefore, Il-1β appears to be a very important effector cytokine, especially for the maintenance of a SASP after primary initiation of the SASP by the induction of “inflammaging” due to a cellular stressor.…”
Section: Discussionsupporting
confidence: 91%
“…A microarray study has shown that senescent VSMCs reveal differential regulation of Matrix Gla Protein, Bmp-2, Osteoprotegerin, and Il-1β ( 34 ). In our own previous work, we demonstrated that plasma concentrations of Il-1β and Il-6 were significantly increased in rats treated with azathioprine, another known cellular stressor and ROS inducer, over a 24-weeks period of treatment ( 35 ). Increased expression of Il-1β and Il-6 was also detected in the aortas of treated rats, which were associated with increased expression of the osteogenic proteins Bmp-2, Alp and Cbfa1 ( 35 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The current study aims to establish and validate a method to investigate these biomechanical properties in the process of vascular calcification using an ex vivo setting. For the induction of vascular calcification, two inducers known from in vitro and in vivo settings were used: high phosphate medium and azathioprine (AZA) [7,8]. The results clearly demonstrate that the biomechanical properties were distinguishable between control and stimulation, and therefore provide novel markers to describe vessel functionality during calcification progression.…”
Section: Introductionmentioning
confidence: 94%
“…The NACHT, LRR, and PYD domains-containing protein 3 (NLRP3) inflammasome is an essential component of the innate immune system and can induce the secretion of the proinflammatory cytokine interleukin 1 beta (IL-1β) in a caspase-1-dependent manner ( 82 , 83 ). Moreover, IL-1β can activate the secretion of the receptor activator of NF-κB ligand, which promotes the formation of osteoclasts, leading to VC ( 84 , 85 ).…”
Section: Endoplasmic Reticulum Stress and Vascular Calcificationmentioning
confidence: 99%